Pengaruh Pemberian Probiotik Terenkapsulasi Pada Pakan Ayam Petelur Terhadap Kolesterol telur Ayam - Zaraswati Dwyana; Ambeng Ambeng; Nur Haedar; Nurul Nasikha (Jurnal Ilmu Alam dan Lingkungan, 2019)
This study aims to determine the effect of probiotic administration encapsulated on the cholesterol content of egg laying eggs. Probiotics are given to laying hens (phase layer), once a day for 4 weeks orally. In this study a completely randomized design (CRD) was used with three treatments, namely, probiotic encapsulated lactic acid bacteria (BAL) (E1), commercial probiotics (E2), and without probiotics (E0) with 4 replications. The variables observed in this study were encapsulated probiotic viability, egg weight (g), egg index (%), and total egg cholesterol content (mg / g). The results showed that the viability of probiotic bacteria decreased by 3.34 cfu / g after 4 weeks of storage at 4OC. Average egg weight at E0; E1; and E2 are 62.63 g, 62.67 g, and 64.15 g. Average egg index at E0; E1; and E2 are 71.13%, 75.54%, and 77.2%. The average cholesterol content at E0; E1; and E2 is 3.75 mg / g, 3.25 mg / g and 3.25 mg / g. The administration of encapsulated probiotics did not affect the quality of egg weight but it affected the egg index and total cholesterol content of egg laying eggs.